A filológiai tudás mint határtapasztalat: Kosztolányi Dezső publikálási gyakorlatáról - Bengi, László (Studia Litteraria, 2018)
Publication practices during the early decades of the 20th century had a significant impact on the approach to literary works for both writers and readers. The majority of authors, including Kosztolányi, published the same work several times in different papers. The genealogy of texts is pervaded by the effects of contingency and unintentionality due to the lack of authorial, and sometimes editorial, control in the extensive and variable dissemination of works. Nevertheless, since the interaction of variants and their contexts can be conceived of as a mutual process, the mentioned publication practices also give rise to the possibility that a textual frame can be built around a work by re-publishing connected writings of the author’s oeuvre in the same paper within a short period. As an example, i show how Kosztolányi compiled an almost invisible series of short stories about death and suicide around the publication of one of his novels in the middle of the 1920s.